2022
DOI: 10.1002/app.52914
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of hierarchical porous fluoro‐PolyHIPE materials with ultra‐high specific surface area via hypercrosslinking knitting technique

Abstract: Fluoro‐PolyHIPEs with porous structure exhibit an excellent weather resistance for adsorption, separation or catalyst support applications in extreme environments, however, the specific surface area still needs to be improved. In this study, a porous fluorinated material is prepared by using high internal phase emulsion template method, and the porous structure of fluoro‐PolyHIPE (F‐PolyHIPE) is subsequently excavated and modified by the hypercrosslinking “knitting” method. The “knitting” of micropores in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…With the first approach, hierarchically porous polyHIPEs were obtained through the hyper-cross-linking and eventual pyrolysis of emulsion-templated polymers or, more recently, micro/meso/macroporous polyHIPEs were obtained through the hyper-cross-linking and porogen removal of suitably designed interpenetrating polymer networks . The generation of a hierarchical porosity in polyHIPEs has been shown to have significant advantages in adsorption applications, promoting material transport and thus providing efficient access in diffusion-controlled processes such as gas, dye, and solvent uptake. , For example, recently developed hierarchically porous polyHIPEs in which microporous walls have been obtained through hyper-cross-linking, have exhibited highly enhanced specific surface areas (SSAs) and adsorption of CO 2 . , In addition, hierarchically porous polyHIPEs have exhibited enhanced uptake of hydrocarbons such as n -butane with respect to commercially available microporous carbons due to the presence of both macropores for transport and highly microporous walls for adsorption . Similarly, hierarchically porous hyper-cross-linked resins with high microporous fractions have been synthesized to enhance their adsorption capacity, , and hybrid structures have been designed in which the hyper-cross-linked resin is exploited to generate microporosity in mesoporous silica nanoparticles …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the first approach, hierarchically porous polyHIPEs were obtained through the hyper-cross-linking and eventual pyrolysis of emulsion-templated polymers or, more recently, micro/meso/macroporous polyHIPEs were obtained through the hyper-cross-linking and porogen removal of suitably designed interpenetrating polymer networks . The generation of a hierarchical porosity in polyHIPEs has been shown to have significant advantages in adsorption applications, promoting material transport and thus providing efficient access in diffusion-controlled processes such as gas, dye, and solvent uptake. , For example, recently developed hierarchically porous polyHIPEs in which microporous walls have been obtained through hyper-cross-linking, have exhibited highly enhanced specific surface areas (SSAs) and adsorption of CO 2 . , In addition, hierarchically porous polyHIPEs have exhibited enhanced uptake of hydrocarbons such as n -butane with respect to commercially available microporous carbons due to the presence of both macropores for transport and highly microporous walls for adsorption . Similarly, hierarchically porous hyper-cross-linked resins with high microporous fractions have been synthesized to enhance their adsorption capacity, , and hybrid structures have been designed in which the hyper-cross-linked resin is exploited to generate microporosity in mesoporous silica nanoparticles …”
Section: Introductionmentioning
confidence: 99%
“…19,20 For example, recently developed hierarchically porous polyHIPEs in which microporous walls have been obtained through hyper-cross-linking, have exhibited highly enhanced specific surface areas (SSAs) and adsorption of CO 2 . 21,22 In addition, hierarchically porous polyHIPEs have exhibited enhanced uptake of hydrocarbons such as n-butane with respect to commercially available microporous carbons due to the presence of both macropores for transport and highly microporous walls for adsorption. 23 Similarly, hierarchically porous hyper-cross-linked resins with high microporous fractions have been synthesized to enhance their adsorption capacity, 11,24 and hybrid structures have been designed in which the hyper-cross-linked resin is exploited to generate microporosity in mesoporous silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Acid and alkali resistance and mechanical properties tests showed that the polymer has excellent chemical stability and high compressive stress, but the synthesis of the block copolymer is complex and cannot be scaled up. Lin et al 25 prepared fluorinated porous polymers with high porosity and high surface area by a simple method using St, DVB and TFEMA as comonomers through a HIPE combined with hypercrosslinking. These materials also exhibited excellent acid and alkali resistance, hydrophobicity and thermal stability.…”
Section: Introductionmentioning
confidence: 99%